Abstract 128: Endovascular Thrombectomy for Severe Cerebral Venous Thrombosis: A Comprehensive Meta‐analysis Assessing Safety and Efficacy - Hatem Tolba; Sherief Ghozy; Atakan Orscelik; Mariam Abdelghaffar; Hassan Kobeissi; Hazem Ghaith; Alzahraa Abbas; Ramanathan Kadirvel; Waleed Brinjikji; David Kallmes (Stroke: Vascular and Interventional Neurology)
Introduction Cerebral sinus venous thrombosis (CSVT) has traditionally been treated medically with systemic anticoagulation. Recent advances in endovascular therapy (EVT) may represent an alternative treatment to medical therapy for CSVT. We conducted a systematic review and meta‐analysis to evaluate the use of EVT for CSVT. Methods We conducted a systematic literature review using PubMed, Embase, Scopus, and Web of Science. We included studies that reported outcomes following EVT for CSVT. The primary outcome of interest was rate of modified Rankin Scale (mRS) 0‐2. Secondary outcomes of interest were rates of complete, partial, and failed recanalization, mortality, and new or expansion of hematoma. We calculated pooled rates (%) and their corresponding 95% confidence intervals (CI). Results Thirty‐eight studies with 682 patients were included. Rate of mRS 0‐2 was 82.6% (95% CI, 75.3%‐88.0%). Rate of complete recanalization was 60.9% (95% CI, 49.1%‐71.5%), rate of partial recanalization was 34.2% (95% CI, 24.1%‐45.9%), and rate of failed recanalization was 5.4% (95% CI, 3.1%‐9.2%). Rate of mortality was 6.7% (95% CI, 4.1%‐10.8%) and rate of new or expansion of hematoma was 5.1% (2.9%‐8.8%). Conclusion In this systematic review and meta‐analysis, EVT for CSVT was associated with favorable rates of mRS 0‐2 and recanalization. Furthermore, EVT was associated with a promising safety profile. Future prospective, comparative studies are warranted to assess EVT for CSVT.